Comparison of body compositions among endurance, strength, and team sports athletes - Azmy, U.; Rahmaniah, N.; Renzytha, A. R.; Atmaka, D. R.; Pratiwi, R.; Rizal, M., Adiningsih, S.; Herawati, L. (SportMont, 2023)
Regular monitoring and evaluation of body composition determine an athlete`s output, such as their probability of winning competitions. The purpose of this study was to analyze the differences in athletes` body composition among several sports categories. The data collected were on 251 athletes aged 20 to 30 years during the pre-competition period. The subjects were divided into three groups: endurance, power, and team sports. SECA 515mBCA was used to analyze the athletes` body composition, which included their body fat percentage (BFP), fat mass (FM), fat-free mass (FFM), skeletal muscle mass (SMM), total body water (TBW), and extracellular water (ECW). The results showed that all body composition parameters were lowest in the endurance category. Fat composition was lowest in the endurance category but did not differ significantly between categories in male athletes. Meanwhile, in female athletes, there was a significant difference in FM between sports categories (p=0.009). FFM, SMM, TBW, and ECW differed significantly between categories (p<0.05). In female athletes, these variables were higher in the team sports category, as opposed to the power category among male athletes. This study concluded that there were differences in lean body mass composition between sport categories, while fat mass did not differ between sport categories in male athletes. This can be attributed to the differences in training programs and needs of each sport category in maximizing performance. These findings can provide advice to sports professionals that each sport category has its own body composition specifications.